EFFECT OF YOGA ON DURATION OF THE SECOND STAGE OF LABOR AND PERINEAL RUPTURE IN PRIMIGRAVIDA MOTHERS - Ana Setyowati; Suhartono Suhartono; Ngadiyono Ngadiyono; Rr Sri Endang Pujiastuti; Dyah Dyah (Belitung Nursing Journal, 2017)
Objective: To determine the effect of yoga on the duration of the second stage of labor and perineal rupture in primigravida mothers. Methods: This was a quasi-experimental study with posttest group only design. The study was conducted in the Public Health Center of Pekalongan, Central Java, Indonesia from December 2016 until January 2017. There were 50 mothers selected using purposive sampling, which 25 assigned in the experiment and control group. Independent t-test and Chi Square test were used for data analysis. Results: There was a statistically significant difference in the duration of second stage of labor (p=0.000) and perineal rupture (p=0.001) between experiment and control group. Conclusion: There was a significant effect of yoga on the duration of the second stage of labor and perineal rupture in primigravida mothers. Therefore, yoga is recommended for midwife to be included in the antenatal care.